Assessment of effectiveness expenditures of pharmacy information system in medication-related services in hospitals of Iran - Mirzaeian, Razieh; Isfahani, Sakineh Saghaeiannejad; Mobasheri, Mahmoud; Rad, Javad Sharifi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: On average, 40% of the gross income of each country is devoted to the health care with medication expenditures accounting for 19% of the total expenses. Less than ¼ of the medication expenditures is allocated to the inpatients department. The measures taken regarding the management of expenditures when selecting and implementing the strategies for managing medication expenditures have made the pharmacists to take the quality issues as well as the safety of the patients into account. Methods: The present research intends to explore the expenditures of effectiveness of Pharmacy Information System (PIS) for the medication services as far as effectiveness of delivered services is concerned in some selected hospitals in the city of Isfahan, Iran. The present research of applied and descriptive-analytical nature was conducted in the hospitals in the City of Isfahan, Iran. Instruments used for collecting data included self designed checklist conforming to the guidelines of the American Society of Health-System Pharmacists (ASHP) the validity of which was assessed based on the viewpoints of the expert professors. The data gathered by interview and observation methods. Then, they were analyzed using non-parametric tests of Mann-Whitney and the Wilcoxon tests and SPSS software (11.5 version). Results: The highest rate of the expenditures of the effectiveness of the pharmacy information system belonged to the teaching hospitals with a mean score of 48.5%, while the lowest rate was found to be for private hospitals with a mean score of 28.1%. Based on the findings of the Wilcoxon test, no statistically significant difference was observed among the hospitals in terms of effectiveness-related expenditures. Conclusions: Given the results of the study, it can be noted that a successful plan for managing the medication-related expenditures must be information-based.